Left atrial functional assessment and mortality in patients with severe aortic stenosis. (8th February 2021) - Ferreira, J; Goncalves, V; Marques, P; Martins, R; Monteiro, S; Teixeira, R; Goncalves, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: Aortic valve stenosis (AS) is the most common primary valvular heart disease leading to surgical or percutaneous aortic valve replacement (AVR) in Europe. Both symptoms and systolic dysfunction can appear late in the course of the disease, being often synonym of irreversible damage to the myocardium when found. Thus, there is a necessity to find other sensitive markers present at an earlier stage of the disease.  Purpose: Our primary aim is to clarify the relationship between LA function measured at severe AS diagnosis (evaluated by means of volumetric assessment) and all-cause mortality during follow-up. Methods: We retrospectively evaluated patients diagnosed with severe AS for the first time at our echocardiography laboratory. We evaluated all 3 left atrial (LA) functional phases (reservoir, conduit and pump) by measuring LA volumes at different timings of cardiac cycle. Treatment strategy was decided according to heart team consensus and own patient decision. We divided patients into groups according to terciles of LA reservoir, conduit and pump function. Primary outcome was defined by the occurrence of all-cause mortality during follow-up. Results: After exclusion criteria, a total of 451 patients were included in the analysis (aged 74 ±11years, 54% male) and were followed during a median period of 73 months (interquartile range 44.5). A total of 55.8% of patients underwent AVR and 45, 5% of patients registered the primary outcome. Left atrial emptying fraction (LAEF) was the best LA functional parameter in discriminating primary outcome (AUC 0.840, p < 0.001), even when compared to left ventricular ejection fraction, aortic valve area, aortic mean pressure gradient and aortic Vmax. Patients in the lower tercile of LAEF were older, had greater comorbidities, had greater AS severity, with greater degree of diastolic disfunction. After adjustment for clinical and demographic variables, cumulative survival of patients with LAEF <37% and LAEF 37 to 53% relative to patients with LAEF ≥54% remained significantly lower (adjusted HR 19.04, 95% CI 8.30-43.67, P < 0.001 and adjusted HR 4.09, 95% CI 1.85-9.06, P = 0.001). Survival was also higher in patients with LAEF 37 to 53% when compared to patients with LAEF <37% (adjusted HR 0.22, 95% CI 0.13-0.37, P < 0.001). All associations remained true after adjustment for AVR (LAEF <37% versus LAEF 37 to 53% and LAEF ≥54%, respectively, adjusted HR 3.97, 95% CI 1.80-8.78, P = 0.001 and adjusted HR 13.95, 95% CI 5.98-32.54, P < 0.001, respectively) Conclusion(s) In patients with a first diagnosis of severe AS in hospital setting, LA function assessed by volumetric parameters is an independent predictor of all-cause mortality. Compared to classical severity parameters, different LA functional parameters were found to be more potent predictors of death. These data can be useful in clinical practice for risk stratification and therefore for decision of timing for AVR.